ANALISIS PERLAKUAN JOINT BALOK KOLOM TERHADAP BEBAN SIKLIK DENGAN PENAMBAHAN SENGKANG PADA JOINT SESUAI SK SNI T-15-1991-03 - Zardan Araby; Samsul Rizal; Mochammad Afifuddin; Abdullah Abdullah (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2021)
Joint beam-columns are the main structural components that function to support other structural loads. The beam-column relationship area is a critical area that needs to be designed to be truly accurate so that it can dissipate energy properly well in the event of an earthquake happen. As a structural component with the role and function, column joint beams occupy important positions in the building. The ability of column joint beams to deform cyclic loads in the inelastic region provides a good structure, so as to minimize damage caused by earthquake shaking. The failure of column joint beams directly affects other structural components associated with it. The purpose of this study was to study the ability of building structures on concrete column beam joint elements to resist cyclic load with reinforcement reinforcement in accordance with SK SNI T-15-1991. Test specimens amounted to 1 (one) with a concrete quality of 19.17 MPa. The beam measuring 120 x 30 x 40 cm, column measuring 30 x 30 x 200 cm using reinforcement 8, 13.4 mm with a melting voltage (fy) 310,03 MPa and stirrup reinforcement Ø9.8-100 mm with melting stress (fy) 374,59 MPa. The test was carried out by giving a cyclic load to the end of the beam with 0.75 mm, 1.5 mm, 3 mm, 6 mm, 12 mm, 24 mm and monotonic loading, until the specimen was destroyed. The results achieved in this study are the use of reinforcement reinforcement according to SK SNI T-15-1991-03 the capacity of the cyclic load produced is higher, namely 6,97 tf (press) and 5.09 tf (tensile).